Accustoming Students’ Polite Language Through Mother: Its Barriers - Rosyiidah, Afiifah Al; Hikmah, Darul (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2021)
This article principally discusses one of the enticing issues which is to accustom language politeness. This study focuses on the use of MOTHER (Madurese Theme Role Play) to accustom students’ language politeness at university level particularly at University of Trunojoyo Madura. It aims to discover and explain how maxim of  GSP (General Strategy  of  Politeness) are utilized in the Madurese Theme Role Play. Moreover, it also aims to reveal some barriers in utilizing MOTHER to accustom students’ language politeness.This study uses qualitative design of the research. In order to get the data, observation and depth interview are applied. In addition, field-notes are used during the observation and interview to collect the data. Besides, audio-recording is also conducted to gain additional detailed information that is likely missing on the field-notes. Interactive model of data analysis is applied to analyze the data, including data reduction, data display, and data verification. The result of the study shows that ten maxims of politeness in the implementation of Madurese Theme Role Play are found. The eighty-three data are classified into ten maxims of politeness: generosity maxim, tact maxim, approbation maxim, modesty maxim, obligation (of S to O) maxim, Obligation (of O to S) maxim, agreement maxim, opinion reticence maxim, sympathy maxim, and feeling reticence maxim. Besides, the seven barriers are encountered during the implementation of MOTHER to accustom students’ language politeness, including students’ difficulties to coordinate and cooperate with the team, to elaborate the plot of the role play, to discover references and find attractive story ideas deal with Madurese themes, to create polite dialogues of the role play, to specifies the context (to whom) the dialogue is addressed to, and to determine the title of role play. Keywords: language politeness, Madurese theme role play